FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN MINAT IBU TERHADAP PENGGUNAAN ALAT KONTRASEPSI IMPLANT DI PUSKESMAS OME KOTA TIDORE KEPULAUAN - Susanti, Susanti; Wowor, Mona; Hamel, Rivelino (Universitas Sam Ratulangi)
Abstract: Method of contraception is easy clue to the effects that impact on the body will not be know for not using it. Factors that relafe to the mother’s interest against the use of contraception implants including: knowledge, education, the economy. The research was conducted on Juni in Ome health centers Tidore city. The purpose of this Study was to find out what factors relate to the mother’s interest against the use of implanted contraceptives in puskesmas Ome Tidore city. The design utilizes crosst sectional , with Sampling pruposing selection. The sample consists of 88 respondents data collection will done questionnaires who made the researchers and in the contents by respondents . next the data is processed in a frequency distribution table. The research results obtained by the factors that relate to the mother’s interest in the use of implanted contraceptive in puskesmas Ome tidore city. Which is reviewed from a good : knowledge factors as much as respondents (77,3%) and lack of knowledge as much as 68 respondents (22,3 %) higher education factors > high school 47 respondents (53,4%) and more than high school 41 respondents (46,6%). Good economi factors as much as 48 respondents (54,5%) and weak 40 respondents (45,5%). Conclusions in this study there was a meaningful relationship between knowledge, education, and the economy. Keywords: Knowledge, educations, economy Abstrak: Metode alat kontrasepsi merupakan hal yang mudah karena efek yang berdampak terhadap tubuh tidak akan diketahui selama belum menggunakannya. Faktor-faktor yang berhubungan dengan minat ibu terhadap penggunaan alat kontrasepsi implant meliputi: pengetahuan, pendidikan, ekonomi. Penelitian ini dilakukan pada bulan Juni di puskesmas Ome Kota Tidore Kepulauan. Tujuan penelitian ini untuk mengetahui faktor apa yang berhubungan minat ibu terhadap penggunaan alat kontrasepsi implant di puskesmas Ome Kota Tidore Kepulauan. Desain penelitian ini menggunakan analitik dengan pendekatan cross sectional, dengan pemelihan purposive sampling. Sampel berjumlah 88 responden. Pengumpulan data dilakukan kuisioner yang dibuat peneliti dan diisi oleh responden. Selanjutnya data diolah dalam tabel distribusi frekuensi. Hasil penelitian di peroleh faktor-faktor yang berhubungan minat ibu terhadap penggunaan alat kontrasepsi implant di puskesmas Ome Kota Tidore Kepulaun. Yaitu ditinjau dari faktor pengetahuan yang baik sebanyak 20 responden (77,3%) dan pengetahuan kurang sebanyak 68 responden (22,3%), faktor pendidikan tinggi > SMA 47 responden (53,4%) dan > SMA 41 responden (46,6%), faktor ekonomi baik sebanyak 48 responden (54,5%) dan lemah 40 responden (45,5%). Kesimpulan dalam penelitian ini ada hubungan bermakna antara pengetahuan, pendidikan, dan ekonomi. Kata kunci : Pengetahuan, pendidikan, ekonomi